1999
DOI: 10.1038/sj.bjc.6690448
|View full text |Cite
|
Sign up to set email alerts
|

BPD-MA-mediated photosensitization in vitro and in vivo: cellular adhesion and β1 integrin expression in ovarian cancer cells

Abstract: Summary Benzoporphyrin derivative monoacid (BPD-MA) photosensitization was examined for its effects on cellular adhesion of a human ovarian cancer cell line, OVCAR 3, to extracellular matrix (ECM) components. Mild BPD-MA photosensitization (~ 85% cell survival) of OVCAR 3 transiently decreased adhesion to collagen IV, fibronectin, laminin and vitronectin to a greater extent than could be attributed to cell death. The loss in adhesiveness was accompanied by a loss of β 1 integrin-containing focal adhesion plaqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 49 publications
4
53
1
3
Order By: Relevance
“…We and others have shown that collagen IV, laminin, and fibronectin are among the components of the extracellular matrix that are critical to the adhesion and growth of tumor metastases, including ovarian micronodules (8,(71)(72)(73)(74). Laminin and collagen IV are major components in Matrigel, and fibronectin is also present.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that collagen IV, laminin, and fibronectin are among the components of the extracellular matrix that are critical to the adhesion and growth of tumor metastases, including ovarian micronodules (8,(71)(72)(73)(74). Laminin and collagen IV are major components in Matrigel, and fibronectin is also present.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported a biological response of cells following PDT, such as a decrease in cell adhesion (45,46), an increase in cytokines production (47), and an increase in heat shock proteins (48). This study describes the effect of subcurative PDT on prostate cancer cells and reports an increase in VEGF both in vitro and in vivo in an orthotopic prostate cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…Verteporfin (benzoporphyrin derivative, VP) is a photosensitizer that accumulates mainly in mitochondria [61]. Upon light exposure, VP produces singlet oxygen that can react with unsaturated fatty acids and proteins, leading to radical-formation and membrane-leakage.…”
Section: Cell Survival After Pda and Ascorbate Treatmentmentioning
confidence: 99%
“…Using animal models, Verteporfin shows promise for cancer treatment [7,8,9,10]. Verteporfin, as a lipid formulated drug preparation, localizes mainly in lipophilic structures of the mitochondria and endoplasmic reticulum with a small fraction distributed within the cytoplasm [11]. The biological mechanism of phototoxicity in vitro appears in most cases to be mitochondrial induced apoptosis [12], as seen in human promyelocytic leukemia HL-60 [13], mouse P815 mastocytoma [14], and HeLa epidermoid carcinoma [15].…”
Section: Introductionmentioning
confidence: 99%